Love & profit the art of caring leadership - Autry, James A.; Gray, Jules ([St. Paul, Minnesota] : StarThrower, 1993)
Helps managers gain powerful new insight into how to lead others with honesty, compassion and strength
With James A. Autry
DVD format
Keywords: Job enrichment; caring; Interpersonal relations; Organizational change; Personnel management